Die Gonokokkeninfektion in Österreich: Eine Langzeitbeobachtung der Prävalenz und Resistenzentwicklung von 1999 bis 2014. (November 2015) - Stary, Angelika; Heller‐Vitouch, Claudia; Binder, Michael; Geusau, Alexandra; Stary, Georg; Rappersberger, Klemens; Komericki, Peter; Hoepfl, Reinhard; Haller, Maria
Summary: Background and objectives: The increase in minimum inhibitory concentrations (MICs) of cephalosporins for Neisseria gonorrhoeae has given rise to concerns regarding potentially untreatable gonococcal infections. The goal was to ascertain the prevalence of gonorrhea in a Viennese patient group and determine resistance patterns. Another objective was to evaluate resistance profiles and MIC values of gonococcal isolates in an Austria‐wide surveillance project. Patients and methods: From 1999 to 2014, 350 000 individuals were tested for gonococci at the Viennese Outpatient Clinic. In addition, from 2010 to 2014, the MICs of recommended antibiotics was determined in 3584 gonococcal isolates, initially by agar dilution and breakpoint determination, and, from 2012 onwards, by Etest®. Results: During the observation period, the prevalence of gonorrhea increased eightfold, with a significantly greater number of quinolone, penicillin, and tetracycline‐resistant strains. In gonococcal strains isolated from across Austria, there was an increase in cefixime and ceftriaxone MICs toward breakpoints. Twenty‐one isolates showed cefixime resistance, and while there was an increase in azithromycin resistance from 0.9 % (2013) to 3.2 % (2014), no resistance to ceftriaxone was observed. Conclusion: Currently, there is no imminent risk of untreatable gonorrhea in Austria. However, continuing the use of gonococcal cultures as a diagnostic tool for establishing resistance profiles is essential in order to monitor trends in the development of Neisseria (N.) gonorrhoeae resistance.